The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1103/physrevb.72.045414
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra and thermal stability analysis of0.4nmfreestanding single-walled carbon nanotubes

Abstract: The thermal stability of ultrasmall 0.4 nm single-walled carbon nanotubes ͑SWNTs͒ are studied by means of Raman-scattering measurements under a vacuum. The 0.4 nm SWNTs are very stable when they are confined inside the channels of the AlPO 4 -5 zeolite crystal. When these SWNTs are extracted from the channels into free space, however, they become thermally unstable because of the strong curvature effect. The in situ Raman-scattering measurement under 1 ϫ 10 −5 mbar shows all three structures of the 0.4-nm-size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
3
11
0
3
Order By: Relevance
“…Although nanotubes can stand very high annealing temperatures [11], the smaller tubes with high curvature are very reactive. The strong curvature was also reported to trigger the destruction of ultrathin SWNTs at the elevated temperature even in vacuum [12]. Our results are in good agreement with this observation.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Although nanotubes can stand very high annealing temperatures [11], the smaller tubes with high curvature are very reactive. The strong curvature was also reported to trigger the destruction of ultrathin SWNTs at the elevated temperature even in vacuum [12]. Our results are in good agreement with this observation.…”
supporting
confidence: 94%
“…However, it has been also reported that for the small diameter tubes, the change of D line position is very pronounced. For instance, the D line in 0.4 nm tube is about 1239 cm À1 with higher intensity due to a significant bending of bonds in small tubes because of curvature effect [12]. The observed 1250 cm À1 is very close to the D-line value and the diameter of inner tube is larger than 0.4 nm.…”
mentioning
confidence: 83%
“…C 1 and C 2 indicate the two carbon atoms in the bridge site. previous studies, both theoretically [42] and experimentally [43,44], wherein the (5,0) SWCNT was found to be significantly more robust than the (3,3) and (4,2) SWCNTs, all three of which have similar diameters. So with the exception of the (5,0) SWCNT, a trend can be generalized that relates the charge transfer with the R 0 .…”
Section: Adsorption Of Atomic Oxygenmentioning
confidence: 91%
“…3, Raman spectrum of the 4-Angstrom carbon nanotubes is characterized by three significant peaks at 510 cm À1 , 550 cm À1 , 580 cm À1 in the RBM region, attributable to the (4,2), (5,0) and (3,3) nanotubes, respectively. 27 It is noted that the D band splits into three major peaks, a phenomenon which still remains unexplained. It should be noted that the large curvature of the ultra-small SWNTs introduces a re-hybridization of the s * and p * bands, thereby leading to a softening of the RBM mode.…”
Section: Raman Characteristicsmentioning
confidence: 99%